Implementation Of UI/UX Concepts And Techniques In Web Layout Design With Figma - Santoso, Miftah Faroq (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Technological trends are always dynamic and experiencing rapid development, especially the internet with many sites emerging, both formal and entertainment (intertain). This requires a web developer, especially in terms of appearance, to always innovate in order to provide a good user experience, intuitive design, and easy to use by all groups. Of course, in designing an attractive interface page, you have to know the needs of the user, in order to optimize existing features, for that UI/UX concepts and techniques need to be applied in designing the interface. In this research trial using the Figma tool as the main tool starting from designing, wireframing to the prototyping process. The test results found that by applying UI/UX concepts and techniques to the interface design the design is more consistent, solid, harmonization, color alignment, font type and size according to the design system that has been determined.